The effect of lifestyle modification and glycemic control on the efficiency of sildenafil citrate in patients with erectile dysfunction due to type-2 diabetes mellitus. (2nd October 2015) - Kirilmaz, Utku; Guzel, Ozer; Aslan, Yilmaz; Balci, Melih; Tuncel, Altug; Atan, Ali
Abstract: Objectives : We evaluated the effect of lifestyle modifications and glycemic control on the efficiency of sildenafil citrate in patients with type-2 diabetes (T2DM) and erectile dysfunction (ED). Methods : Eighty-three men with ED due to T2DM were included in the study. The Group 1 ( n = 41) patients received lifestyle modifications (diet and exercise), and medical treatment for intensive glycemic control. In Group 2 ( n = 42), in addition to the intensive glycemic control, the patients were given sildenafil citrate® 100 mg for 2–3 per weeks. The changes in ED were compared between the two groups after three months of treatment. Results : The mean age was 54.9 ± 9.1 (26–75) years. An increase in the IIEF-5 scores was observed in 23 of 41 patients in Group 1 (44.2%) and 29 of 42 in Group 2 (55.8%). When the changes of the IIEF-5 scores were evaluated, the mean increase was 2.5 in Group 1, and 5.0 in Group 2 ( p = 0.012). The mean IIEF changes according to the duration of diabetes were 4.8 in <5 years, 3.6 in 5–10 years and 1.6 in >10 years ( p = 0.021). Conclusions : Glycemic control and lifestyle changes are not solely adequate for a better sexual function in ED due to diabetes, and sildenafil citrate should be used additionally.